Synergetic Effect of In and Ag Co-doped ZnS for Enhanced Photocatalytic Hydrogen Evolution under Visible Light Irradiation - Melody, Kimi; Leny, Yuliati; Mustaffa, Shamsuddin (Trans Tech Publications, 2014)
In (Indium) and Ag (Argentum) co-doped ZnS photocatalysts were successfully prepared by hydrothermal method to extend the light absorption of ZnS to the visible light region. The concentration of In was constant while for Ag was varied to optimize the photocatalytic activity. The In and Ag co-doped ZnS (Zinc Sulfide) photocatalysts showed smaller band gap energy compared to single doped In(0.1)-ZnS and undoped ZnS. The photocatalytic activity of In and Ag co-doped ZnS photocatalysts was evaluated from the amount of hydrogen produced. The hydrogen evolution rate from aqueous solution containing Na2SO3 (Sodium Sulfite) and Na2S (Sodium Sulfide) as sacrificial reagent under visible light irradiation obtained from In and Ag co-doped ZnS is higher compared to the single doped In(0.1)-ZnS when optimum amount of Ag dopant was added. The highest photocatalytic activity is observed for In(0.1),Ag(0.01)-ZnS with hydrogen production rate of 26.82 μmol/h. The higher performance of this photocatalyst is ascribed to the extended visible light absorption, efficient charge separation as well as improved electron transfer associated with synergistic effect of appropriate amount of In and Ag co-doped ZnS.